Preparation method of flexible photovoltaic glass for curved surface

Ultra-thin flexible glass was prepared by femtosecond laser cutting and chemical etching, and the surface was coated with silver, nickel, silicon oxide and molybdenum disulfide quantum dot composite graphene layers, solving the high temperature stability and light transmission of photovoltaic glass In addition, high-efficiency photovoltaic glass preparation has been achieved.

CN119191724AInactive Publication Date: 2024-12-27JIANGSU SIMBA NEW MATERIAL TECH CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411298250.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing photovoltaic glass preparation technology is difficult to adapt to the requirements of high light transmission and thinning, especially in the preparation of ultra-thin flexible glass and high temperature stability. The tiny cracks caused by laser cutting are difficult to avoid, affecting the durability of the glass.

Method used

Ultra-thin flexible glass is prepared by femtosecond laser cutting and chemical etching, and the surface is coated with silver, nickel, silicon oxide and molybdenum disulfide quantum dot composite graphene layers to improve conductivity and stability through multi-layer film structure. and light transmittance.

Benefits of technology

The effect of high temperature stability, high light transmission and low resistance is achieved, and the tiny cracks caused by laser cutting are avoided, the high temperature resistance and stability of the glass are improved, and the light transmittance is enhanced.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method of flexible photovoltaic glass for a curved surface, and relates to the technical field of photovoltaic glass. According to the invention, a femtosecond laser cutting mode is firstly adopted, the glass is cut into a required size, and then thinning is carried out, so that the glass has flexibility, nano-scale micro cracks generated by laser cutting can be etched, and the high temperature resistance of the glass is improved. The silver film layer and the nickel film layer are deposited on the surface layer of the glass, so that the conductivity is improved, and meanwhile, a buffering effect is achieved; plating a silicon oxide film layer; and finally, the graphene layer is compounded with molybdenum disulfide quantum dots, graphene has excellent electron transmission performance, growth of semiconductor nanoparticles is effectively inhibited, and the surface of the graphene layer is uniformly loaded with the quantum dots. The adjustable and controllable band gap structure of the molybdenum disulfide quantum dots improves the light absorption and light transmission of the graphene film. The multiple layers of films generate an optical interference effect, so that the reflectivity is reduced, and the light transmittance is improved. The prepared glass has the effects of high-temperature stability, high light transmittance and low resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photovoltaic glass, and in particular to a method for preparing flexible photovoltaic glass for curved surfaces. Background Art

[0002] Photovoltaic glass is mainly used for the packaging of solar photovoltaic power generation and solar thermal components. As one of the clean, efficient and inexhaustible green energy technologies of the future, the application of photovoltaic technology has become more and more extensive in recent years. The solar photovoltaic industry has become the fastest growing field in the energy market. In 2013, the national cumulative installed capacity of photovoltaic power generation was only 19.12GW, and the power generation was only 9 billion kWh. By 2019, the installed capacity increased to 201.3GW, and the photovoltaic power generation reached 221.3 billion kWh. The photovoltaic industry has shown explosive growth.

[0003] With the advancement of technology and market requirements, double-glass modules have been mass-produced, and photovoltaic glass has developed towards large-scale and thin-type. In order to occupy market share and improve corporate competitiveness, photovoltaic manufacturers have gradually developed towards full oxygen combustion and large kilns. Today, the preparation technology of photovoltaic glass is not enough to meet the requirements of high transparency and thinness. At present, the preparation processes of ultra-thin flexible glass mainly include float method, overflow down-draw method, narrow slit down-draw method, chemical thinning method and secondary down-draw method. On the basis of ultra-thin flexible glass, the preparation of flexible photovoltaic glass with high light transmittance and stability by laminating is the research direction of this invention. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing flexible photovoltaic glass for curved surfaces to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing flexible photovoltaic glass for curved surfaces, comprising the following preparation steps:

[0006] (1) Using a femtosecond laser to cut a large glass raw material with a thickness of 0.6 mm into small pieces of glass of required size; washing the cut small pieces of glass with deionized water for 3 times, drying at 50° C. for 3 h, thinning the dried small pieces of glass, placing them in an etching tank and etching them with an etchant, with the etching liquid being level with the upper layer of the glass without contaminating the upper surface of the glass, and the rest being fully immersed until the thickness of the glass is reduced to 0.02-0.06 mm, carefully taking out the glass, washing it with deionized water for 3 times, and finally drying it at 50° C. for 3 h, thereby obtaining ultra-thin flexible glass;

[0007] (2) The thiol graphene aqueous solution after ultrasonic treatment for 24 hours and the molybdenum disulfide quantum dot ethanol / water solution are mixed in a volume ratio of 1:0.5-2.5, the ultrasonic power is 35kHz, the solid-liquid ratio of the thiol graphene aqueous solution and the molybdenum disulfide quantum dot aqueous solution is 1:30, and the oil bath heating and reflux are used. The heating time is 0.5-4.5h and the heating temperature is 40-120°C. The product solution is allowed to stand for 24h to precipitate, and then centrifuged at 1000rpm for 20min. The lower layer of solid is removed and washed with ethanol. The whole process of precipitation, centrifugation and washing is repeated 3 times, and then dried at 80°C for 6h to obtain molybdenum disulfide quantum dot composite graphene powder;

[0008] (3) Loading ultra-thin flexible glass, setting the parameters of the coating machine, and using a horizontal fully automatic continuous magnetron sputtering coating machine to coat each layer of film at a coating temperature of 300°C; first, using pure silver as a target material, a silver film layer is deposited on the surface of the ultra-thin flexible glass; then using high-purity nickel as a target material, a nickel film layer is deposited on the surface of the silver film layer; then opening two silicon targets, introducing oxygen and nitrogen, and performing reactive sputtering to deposit a silicon oxide film; adding molybdenum disulfide quantum dot composite graphene powder to ethylene glycol in proportion, ultrasonically dispersing for 5 hours, and the ultrasonic power is 40kHz to obtain a molybdenum disulfide quantum dot composite graphene powder dispersion, and evenly spraying the molybdenum disulfide quantum dot composite graphene powder dispersion on the surface of the ultra-thin flexible glass after the silicon oxide film is deposited, and drying at 50°C for 4 hours to obtain a flexible photovoltaic glass for a curved surface.

[0009] Furthermore, the large glass raw material in step (1) is flat glass produced by a float process.

[0010] Furthermore, the values ​​of the femtosecond laser cutting process in step (1) are: laser single pulse energy is 100 μJ, laser scanning speed is 5-15 mm / s, repetition frequency is 80-120 kHz, and defocus is -100 μm.

[0011] Furthermore, the method for preparing the etchant in step (1) is to mix hydrofluoric acid, hydrochloric acid, phosphoric acid, silane coupling agent KH550, sodium dodecyl sulfate, and deionized water in a mass ratio of 15:5-7:1.2-1.4:0.03:0.01:20.

[0012] Furthermore, in the molybdenum disulfide quantum dot ethanol / water solution in step (2), the volume ratio of ethanol to water is 1:1.

[0013] Furthermore, in step (3), the thickness of the silver film layer is 8-12 nm.

[0014] Furthermore, in step (3), the thickness of the nickel film layer is 1-3 nm.

[0015] Furthermore, in step (3), the thickness of the silicon oxide film layer is 40-60 nm.

[0016] Furthermore, in step (3), the ratio of molybdenum disulfide quantum dot composite graphene powder to ethylene glycol is 1.5 mg: 1 ml.

[0017] Furthermore, in step (3), the thickness of the molybdenum disulfide quantum dot composite graphene film layer is 200-400nm.

[0018] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0019] The present invention combines laser cutting technology with chemical etching to prepare ultra-thin flexible glass, and then coats it with: a silver film layer, a nickel film layer, a silicon oxide film layer, and a molybdenum disulfide quantum dot composite graphene film layer to make flexible photovoltaic glass to achieve high temperature stability, high light transmittance, and low resistance.

[0020] First, the present invention combines the laser cutting process with the chemical etching method to prepare ultra-thin flexible photovoltaic glass. When using the ordinary laser cutting method, the thermal expansion and contraction caused by the temperature generated by the laser cutting will cause tiny cracks on the edge of the small-sized flat glass obtained by cutting. In particular, when the ultra-thin flexible photovoltaic glass prepared by the present invention has a thickness of less than 0.1 mm, laser cutting is difficult to perform. The present invention first performs laser cutting on the thin flat glass to cut it into the required size, and then thins it by chemical etching, so that the thickness of the glass is less than 0.1 mm and it is flexible. At the same time, the nano-scale tiny cracks generated by the laser cutting can be etched away, so as to prevent the photovoltaic glass from being more easily cracked and broken due to thermal expansion and contraction at high temperature during use, thereby improving the high temperature resistance of the glass.

[0021] Secondly, the ultra-thin flexible glass is coated; a silver film layer is first deposited on the glass surface, and its good conductivity reduces the resistance of the film; a relatively thin nickel film layer is then deposited on the surface of the silver film layer to further improve the conductivity while playing a buffering role, preventing the diffusion and oxidation of silver ions in the silver film layer, and improving the stability of the photovoltaic glass; on the nickel film layer is a silicon oxide film layer, which plays a major role in light conversion; on the silicon oxide film layer is a graphene layer composited with molybdenum disulfide quantum dots, which has excellent electron transport properties, and the two-dimensional planar π-conjugated structure can effectively inhibit the recombination of electrons and holes, and can also effectively inhibit the growth of semiconductor nanoparticles, so that the molybdenum disulfide quantum dots are evenly loaded on the graphene surface, thereby realizing the transfer of electrons from excited quantum dots to the graphene surface at a speed of picoseconds; on this basis, the adjustable band gap structure of molybdenum disulfide quantum dots improves the absorption and transmittance of graphene film to light; the multi-layer film produces optical interference, which reduces the reflectivity and improves the transmittance. DETAILED DESCRIPTION

[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0023] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of a flexible photovoltaic glass for a curved surface prepared in the following examples are as follows:

[0024] Resistivity: The resistivity of the examples and comparative examples was measured by a four-probe method.

[0025] Light transmittance: The examples and comparative examples were measured using an Abotek light transmittance instrument.

[0026] High temperature resistance: When the temperature rises to 280°C, put the examples and comparative examples into a constant temperature oven. After 30 minutes, take out the samples from the oven, put them on a wooden table to cool to room temperature, and check for cracks.

[0027] Embodiment 1; (1) A large flat glass prepared by a float process with a thickness of 0.6 mm is cut into small pieces of glass of required size by using a femtosecond laser; the femtosecond laser cutting process is as follows: the laser single pulse energy is 100 μJ, the laser scanning speed is 5 mm / s, the repetition frequency is 80 kHz, and the defocus amount is -100 μm; the cut small pieces of glass are washed with deionized water for 3 times, dried at 50°C for 3 hours, and then the dried small pieces of glass are thinned and placed in an etching tank for etching by an etchant, the etching liquid is level with the upper layer of the glass, does not contaminate the upper surface of the glass, and the rest is completely immersed until the thickness of the glass is reduced to 0.02 mm, the glass is carefully taken out, washed with deionized water for 3 times, and finally dried at 50°C for 3 hours to obtain ultra-thin flexible glass; the etching liquid is a mixture of hydrofluoric acid, hydrochloric acid, phosphoric acid, silane coupling agent KH550, sodium dodecyl sulfate, and deionized water in a mass ratio of 15:5:1.2:0.03:0.01:20;

[0028] (2) The thiol graphene aqueous solution after ultrasonic treatment for 24 hours and the molybdenum disulfide quantum dot ethanol / water solution were mixed in a volume ratio of 1:0.5, the volume ratio of ethanol to water in the ethanol / water solution was 1:1, the ultrasonic power was 35kHz, the solid-liquid ratio of the thiol graphene aqueous solution and the molybdenum disulfide quantum dot aqueous solution was 1:30, and the oil bath was heated with reflux for 0.5 hours and the heating temperature was 40°C. The product solution was allowed to stand for 24 hours to precipitate, and then centrifuged at 1000 rpm for 20 minutes. The lower layer of solid was removed and washed with ethanol. The precipitation, centrifugation and washing process were repeated 3 times, and then dried at 80°C for 6 hours to obtain molybdenum disulfide quantum dot composite graphene powder;

[0029] (3) Loading ultra-thin flexible glass, setting the parameters of the coating machine, and using a horizontal fully automatic continuous magnetron sputtering coating machine to coat each layer of film, with a coating temperature of 300°C; first, using pure silver as a target material, a silver film layer is deposited on the surface of the ultra-thin flexible glass, and the thickness of the silver film layer is 8nm; then using high-purity nickel as a target material, a nickel film layer is deposited on the surface of the silver film layer, and the thickness of the nickel film layer is 1nm; then, two silicon targets are opened, oxygen and nitrogen are introduced, and reactive sputtering is performed to deposit a silicon oxide film, and the thickness of the silicon oxide film layer is 40nm; MoS2 is added MoS2 quantum dot composite graphene powder is added to ethylene glycol, the ratio of MoS2 quantum dot composite graphene powder to ethylene glycol is 1.5 mg:1 ml, ultrasonic dispersion is carried out for 5 hours, the ultrasonic power is 40 kHz, and MoS2 quantum dot composite graphene powder dispersion is obtained. The MoS2 quantum dot composite graphene powder dispersion is evenly sprayed on the surface of the ultra-thin flexible glass with silicon oxide film deposited, the MoS2 quantum dot composite graphene film layer has a thickness of 200 nm, and after drying at 50°C for 4 hours, flexible photovoltaic glass for curved surfaces is obtained.

[0030] Example 2; (1) A large flat glass prepared by a float process with a thickness of 0.6 mm is cut into small pieces of glass of required size by using a femtosecond laser; the femtosecond laser cutting process is as follows: the laser single pulse energy is 100 μJ, the laser scanning speed is 10 mm / s, the repetition frequency is 100 kHz, and the defocus amount is -100 μm; the cut small pieces of glass are washed with deionized water for 3 times, dried at 50°C for 3 h, and then the dried small pieces of glass are thinned and placed in an etching tank for etching by an etchant, the etching liquid is level with the upper layer of the glass, does not contaminate the upper surface of the glass, and the rest is completely immersed until the thickness of the glass is reduced to 0.04 mm, the glass is carefully taken out, washed with deionized water for 3 times, and finally dried at 50°C for 3 h to obtain ultra-thin flexible glass; the etching liquid is a mixture of hydrofluoric acid, hydrochloric acid, phosphoric acid, silane coupling agent KH550, sodium dodecyl sulfate, and deionized water in a mass ratio of 15:6:1.3:0.03:0.01:20;

[0031] (2) The thiol graphene aqueous solution after ultrasonic treatment for 24 hours and the molybdenum disulfide quantum dot ethanol / water solution were mixed in a volume ratio of 1:1.5, wherein the volume ratio of ethanol to water in the ethanol / water solution was 1:1, the ultrasonic power was 35kHz, the solid-liquid ratio of the thiol graphene aqueous solution and the molybdenum disulfide quantum dot aqueous solution was 1:30, and the oil bath was heated with reflux for 2.5 hours at a temperature of 80°C. The product solution was allowed to stand for 24 hours to precipitate, and then centrifuged at 1000 rpm for 20 minutes. The lower layer of solid was removed and washed with ethanol. The precipitation, centrifugation and washing process was repeated 3 times, and then dried at 80°C for 6 hours to obtain a molybdenum disulfide quantum dot composite graphene powder.

[0032] (3) Loading ultra-thin flexible glass, setting the parameters of the coating machine, and using a horizontal fully automatic continuous magnetron sputtering coating machine to coat each layer of film, with a coating temperature of 300°C; first, using pure silver as a target material, a silver film layer is deposited on the surface of the ultra-thin flexible glass, and the thickness of the silver film layer is 10 nm; then using high-purity nickel as a target material, a nickel film layer is deposited on the surface of the silver film layer, and the thickness of the nickel film layer is 2 nm; then, two silicon targets are opened, oxygen and nitrogen are introduced, and reactive sputtering is performed to deposit a silicon oxide film, and the thickness of the silicon oxide film layer is 50 nm; MoS2 is added MoS2 quantum dot composite graphene powder is added to ethylene glycol, the ratio of MoS2 quantum dot composite graphene powder to ethylene glycol is 1.5 mg:1 ml, ultrasonic dispersion is carried out for 5 hours, the ultrasonic power is 40 kHz, and MoS2 quantum dot composite graphene powder dispersion is obtained. The MoS2 quantum dot composite graphene powder dispersion is evenly sprayed on the surface of the ultra-thin flexible glass with silicon oxide film deposited, the MoS2 quantum dot composite graphene film layer is 300 nm thick, and the flexible photovoltaic glass for curved surface is obtained after drying at 50°C for 4 hours.

[0033] Example 3; (1) A large flat glass prepared by a float process with a thickness of 0.6 mm is cut into small pieces of glass of required size by using a femtosecond laser; the femtosecond laser cutting process is as follows: the laser single pulse energy is 100 μJ, the laser scanning speed is 15 mm / s, the repetition frequency is 120 kHz, and the defocus amount is -100 μm; the cut small pieces of glass are washed with deionized water for 3 times, dried at 50°C for 3 hours, and then the dried small pieces of glass are thinned and placed in an etching tank for etching by an etchant, the etching liquid is level with the upper layer of the glass, does not contaminate the upper surface of the glass, and the rest is completely immersed until the thickness of the glass is reduced to 0.06 mm, the glass is carefully taken out, washed with deionized water for 3 times, and finally dried at 50°C for 3 hours to obtain ultra-thin flexible glass; the etching liquid is a mixture of hydrofluoric acid, hydrochloric acid, phosphoric acid, silane coupling agent KH550, sodium dodecyl sulfate, and deionized water in a mass ratio of 15:7:1.4:0.03:0.01:20;

[0034] (2) The thiol graphene aqueous solution after ultrasonic treatment for 24 hours and the molybdenum disulfide quantum dot ethanol / water solution were mixed in a volume ratio of 1:2.5, the volume ratio of ethanol to water in the ethanol / water solution was 1:1, the ultrasonic power was 35kHz, the solid-liquid ratio of the thiol graphene aqueous solution and the molybdenum disulfide quantum dot aqueous solution was 1:30, and the oil bath was heated with reflux for 4.5 hours and the heating temperature was 120°C. The product solution was allowed to stand for 24 hours to precipitate, and then centrifuged at 1000 rpm for 20 minutes. The lower layer of solid was removed and washed with ethanol. The precipitation, centrifugation and washing process were repeated 3 times, and then dried at 80°C for 6 hours to obtain molybdenum disulfide quantum dot composite graphene powder;

[0035] (3) Loading ultra-thin flexible glass, setting the parameters of the coating machine, and using a horizontal fully automatic continuous magnetron sputtering coating machine to coat each layer of film, with a coating temperature of 300°C; first, using pure silver as a target material, a silver film layer is deposited on the surface of the ultra-thin flexible glass, and the thickness of the silver film layer is 12 nm; then using high-purity nickel as a target material, a nickel film layer is deposited on the surface of the silver film layer, and the thickness of the nickel film layer is 3 nm; then, two silicon targets are opened, oxygen and nitrogen are introduced, and reactive sputtering is performed to deposit a silicon oxide film, and the thickness of the silicon oxide film layer is 60 nm; MoS2 is added MoS2 quantum dot composite graphene powder is added to ethylene glycol, the ratio of MoS2 quantum dot composite graphene powder to ethylene glycol is 1.5 mg:1 ml, ultrasonic dispersion is carried out for 5 hours, the ultrasonic power is 40 kHz, and MoS2 quantum dot composite graphene powder dispersion is obtained. The MoS2 quantum dot composite graphene powder dispersion is evenly sprayed on the surface of the ultra-thin flexible glass with silicon oxide film deposited, the MoS2 quantum dot composite graphene film layer has a thickness of 400 nm, and after drying at 50°C for 4 hours, flexible photovoltaic glass for curved surfaces is obtained.

[0036] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that step (1) is different, and step (1) is changed to: a large flat glass prepared by a float process with a thickness of 0.6 mm is washed with deionized water three times, dried at 50°C, and then thinned, and placed in an etching tank for etching by an etchant, the etching liquid is level with the upper layer of the glass, does not contaminate the upper surface of the glass, and the rest is completely immersed until the thickness of the glass is reduced to 0.04 mm, the glass is carefully taken out, washed with deionized water three times, and finally dried at 50°C for 3h to obtain a whole piece of ultra-thin flexible glass; the etching liquid is a mixture of hydrofluoric acid, salt Acid, phosphoric acid, silane coupling agent KH550, sodium dodecyl sulfate and deionized water are mixed in a mass ratio of 15:6:1.3:0.03:0.01:20; a whole piece of ultra-thin flexible glass is cut into small pieces of glass of required size by using a femtosecond laser; the femtosecond laser cutting process is as follows: the laser single pulse energy is 100 μJ, the laser scanning speed is 10 mm / s, the repetition frequency is 100 kHz, and the defocus amount is -100 μm; the cut small pieces of glass are washed with deionized water for 3 times, and dried at 50° C. for 3 hours to obtain the ultra-thin flexible glass; the remaining steps are the same as those in Example 2.

[0037] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that step (3) is different, and step (3) is changed to: loading ultra-thin flexible glass, setting the coating machine parameters, and coating each layer of film using a horizontal fully automatic continuous magnetron sputtering coating machine, and the coating temperature is 300°C; first, using pure silver as a target material, a silver film layer is deposited on the surface of the ultra-thin flexible glass, and the thickness of the silver film layer is 10nm; then opening two silicon targets, passing oxygen and nitrogen, and performing reactive sputtering to deposit a silicon oxide film, and the thickness of the silicon oxide film layer is 50nm; composite molybdenum disulfide quantum dots Graphene powder is added to ethylene glycol, the ratio of molybdenum disulfide quantum dot composite graphene powder to ethylene glycol is 1.5 mg: 1 ml, ultrasonic dispersion is performed for 5 hours, the ultrasonic power is 40 kHz, and a dispersion of molybdenum disulfide quantum dot composite graphene powder is obtained. The dispersion of molybdenum disulfide quantum dot composite graphene powder is evenly sprayed on the surface of the ultra-thin flexible glass on which the silicon oxide film is deposited, the thickness of the molybdenum disulfide quantum dot composite graphene film layer is 300 nm, and after drying at 50° C. for 4 hours, a flexible photovoltaic glass for a curved surface is obtained; the remaining steps are the same as those in Example 2.

[0038] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that step (2) is different, and step (3) is changed to: loading ultra-thin flexible glass, setting the coating machine parameters, and using a horizontal fully automatic continuous magnetron sputtering coating machine to coat each layer of film, and the coating temperature is 300°C; opening two silicon targets, introducing oxygen and nitrogen, and performing reactive sputtering to deposit a silicon oxide film, and the thickness of the silicon oxide film layer is 50nm; adding molybdenum disulfide quantum dot composite graphene powder to ethylene glycol, the ratio of molybdenum disulfide quantum dot composite graphene powder to ethylene glycol is 1.5mg:1ml, ultrasonic dispersion is performed for 5h, the ultrasonic power is 40kHz, and a molybdenum disulfide quantum dot composite graphene powder dispersion is obtained, and the molybdenum disulfide quantum dot composite graphene powder dispersion is evenly sprayed on the surface of the ultra-thin flexible glass on which the silicon oxide film is deposited, the thickness of the molybdenum disulfide quantum dot composite graphene film layer is 300nm, and after drying at 50°C for 4h, a flexible photovoltaic glass for a curved surface is obtained; the remaining steps are the same as Example 2.

[0039] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that there is no step (2), and step (3) is changed to: loading ultra-thin flexible glass, setting the parameters of the coating machine, and coating each layer of film using a horizontal fully automatic continuous magnetron sputtering coating machine, and the coating temperature is 300°C; first, using pure silver as a target material, a silver film layer is deposited on the surface of the ultra-thin flexible glass, and the thickness of the silver film layer is 10nm; then using high-purity nickel as a target material, a nickel film layer is deposited on the surface of the silver film layer, and the thickness of the nickel film layer is 2nm; then opening the two silicon targets, passing oxygen and nitrogen, and performing Reactive sputtering is used to deposit a silicon oxide film with a thickness of 50 nm. Graphene powder is added to ethylene glycol with a ratio of 1.5 mg to 1 ml. Ultrasonic dispersion is performed for 5 h at an ultrasonic power of 40 kHz to obtain a graphene powder dispersion. The graphene powder dispersion is evenly sprayed on the surface of the ultra-thin flexible glass on which the silicon oxide film has been deposited. The graphene film layer has a thickness of 300 nm. After drying at 50° C. for 4 h, a flexible photovoltaic glass for a curved surface is obtained. The remaining steps are the same as those in Example 2.

[0040] Effect example

[0041] Table 1 below shows the performance analysis results of a flexible photovoltaic glass for curved surfaces using Examples 1 to 3 of the present invention and Comparative Examples 1 to 4.

[0042] Table 1

[0043] High temperature resistance Resistivity (Ω·cm) Transmittance(%) Example 1 No cracking <![CDATA[1.02×10 -5 ]]> 92.3 Example 2 No cracking <![CDATA[1.01×10 -5 ]]> 92.7 Example 3 No cracking <![CDATA[1.01×10 -5 ]]> 92.4 Comparative Example 1 There are small cracks <![CDATA[1.03×10 -5 ]]> 92.2 Comparative Example 2 No cracking <![CDATA[1.15×10 -5 ]]> 90.3 Comparative Example 3 No cracking <![CDATA[1.26×10 -5 ]]> 86.5 Comparative Example 4 No cracking <![CDATA[1.20×10 -5 ]]> 86.3

[0044] From the comparison of the experimental data of high temperature resistance of the embodiment and the comparative example, it can be found that the present invention combines the laser cutting process with the chemical etching method to prepare ultra-thin flexible photovoltaic glass; using the ordinary laser cutting method, the thermal expansion and contraction caused by the temperature generated by the laser cutting will cause tiny cracks on the edges of the small-sized flat glass obtained by cutting, especially the ultra-thin flexible photovoltaic glass prepared by the present invention, when the thickness is less than 0.1mm, laser cutting is difficult to perform; the present invention first laser cuts the thin flat glass into the required size, and then thins it by chemical etching, so that the thickness of the glass is less than 0.1m While m is flexible, it can also etch away nano-scale micro cracks caused by laser cutting, preventing photovoltaic glass from cracking and breaking more easily due to thermal expansion and contraction at high temperatures during use, thereby improving the high temperature resistance of the glass; from the comparison of the experimental data of the resistivity of the embodiment and the comparative example, it can be found that the present invention is coated on the surface of ultra-thin flexible glass; a layer of silver film is first deposited on the surface of the glass, and its good conductivity reduces the resistance of the film; and then a relatively thin nickel film is applied on the surface of the silver film layer, which further improves the conductivity and plays a buffering role, preventing the diffusion and oxidation of silver ions in the silver film layer, and improving the stability of the photovoltaic glass. On the nickel film layer is a silicon oxide film layer, which plays a major role in light conversion. On the silicon oxide film layer is a graphene layer compounded with molybdenum disulfide quantum dots. Graphene has excellent electron transmission performance, and the two-dimensional plane π-conjugated structure can effectively inhibit electron-hole recombination, and can also effectively inhibit the growth of semiconductor nanoparticles, so that the molybdenum disulfide quantum dots are evenly loaded on the graphene surface, thereby realizing the transfer of electrons from excited state quantum dots to the graphene surface at a picosecond speed. From the comparison of the experimental data of transmittance between the embodiment and the comparative example, it can be found that the present invention, on this basis, utilizes the adjustable band gap structure of molybdenum disulfide quantum dots to improve the absorption and transmittance of light by the graphene film; the multilayer film produces optical interference, reduces the reflectivity, and improves the transmittance.

[0045] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for preparing flexible photovoltaic glass for curved surfaces, characterized in that: The method comprises the following preparation steps: (1) Using a femtosecond laser to cut a large glass raw material with a thickness of 0.6 mm into small pieces of glass of required size; washing the cut small pieces of glass with deionized water for 3 times, drying at 50°C for 3 hours, thinning the dried small pieces of glass, placing them in an etching tank and etching them with an etchant, with the etching liquid being level with the upper layer of the glass and not contaminating the upper surface of the glass, and the rest being completely immersed until the thickness of the glass is reduced to 0.02-0.06 mm, carefully taking out the glass, washing it with deionized water for 3 times, and finally drying it at 50°C for 3 hours to obtain ultra-thin flexible glass; (2) Mixing the thiol graphene aqueous solution after ultrasonic treatment for 24 hours and the molybdenum disulfide quantum dot ethanol / water solution in a volume ratio of 1:0.5-2.5, the ultrasonic power is 35kHz, the solid-liquid ratio of the thiol graphene aqueous solution and the molybdenum disulfide quantum dot aqueous solution is 1:30, and oil bath heating is adopted with reflux, the heating time is 0.5-4.5h, the heating temperature is 40-120℃, the product solution is allowed to stand for 24h to precipitate, and then centrifuged at 1000rpm for 20min, the lower layer of solid is removed and washed with ethanol, the whole process of precipitation, centrifugation and washing is repeated 3 times, and then dried at 80℃ for 6h to obtain molybdenum disulfide quantum dot composite graphene powder; (3) Loading ultra-thin flexible glass, setting the coating machine parameters, and using a horizontal fully automatic continuous magnetron sputtering coating machine to coat each layer of film at a coating temperature of 300°C; first, using pure silver as a target material, a silver film layer is deposited on the surface of the ultra-thin flexible glass; then using high-purity nickel as a target material, a nickel film layer is deposited on the surface of the silver film layer; then opening two silicon targets, introducing oxygen and nitrogen, and performing reactive sputtering to deposit a silicon oxide film; adding molybdenum disulfide quantum dot composite graphene powder to ethylene glycol in proportion, ultrasonically dispersing for 5 hours, and the ultrasonic power is 40kHz to obtain a molybdenum disulfide quantum dot composite graphene powder dispersion, and evenly spraying the molybdenum disulfide quantum dot composite graphene powder dispersion on the surface of the ultra-thin flexible glass after the silicon oxide film is deposited, and drying at 50°C for 4 hours to obtain a flexible photovoltaic glass for a curved surface.

2. The method for preparing a flexible photovoltaic glass for a curved surface according to claim 1, characterized in that: The raw glass material in step (1) is flat glass produced by the float process.

3. The method for preparing a flexible photovoltaic glass for a curved surface according to claim 1, characterized in that: The values ​​of the femtosecond laser cutting process in step (1) are: laser single pulse energy is 100 μJ, laser scanning speed is 5-15 mm / s, repetition frequency is 80-120 kHz, and defocus is -100 μm.

4. The method for preparing a flexible photovoltaic glass for a curved surface according to claim 1, characterized in that: The method for preparing the etchant in step (1) is to mix hydrofluoric acid, hydrochloric acid, phosphoric acid, silane coupling agent KH550, sodium dodecyl sulfate and deionized water in a mass ratio of 15:5-7:1.2-1.4:0.03:0.01:

20.

5. The method for preparing a flexible photovoltaic glass for a curved surface according to claim 1, characterized in that: In the molybdenum disulfide quantum dot ethanol / water solution in step (2), the volume ratio of ethanol to water is 1:

1.

6. The method for preparing a flexible photovoltaic glass for a curved surface according to claim 1, characterized in that: The thickness of the silver film layer in step (3) is 8-12 nm.

7. The method for preparing a flexible photovoltaic glass for a curved surface according to claim 1, characterized in that: The thickness of the nickel film layer in step (3) is 1-3 nm.

8. The method for preparing a flexible photovoltaic glass for a curved surface according to claim 1, characterized in that: The thickness of the silicon oxide film layer in step (3) is 40-60 nm.

9. The method for preparing a flexible photovoltaic glass for a curved surface according to claim 1, characterized in that: In the step (3), the ratio of molybdenum disulfide quantum dot composite graphene powder to ethylene glycol is 1.5 mg: 1 ml.

10. The method for preparing a flexible photovoltaic glass for a curved surface according to claim 1, characterized in that: In the step (3), the thickness of the molybdenum disulfide quantum dot composite graphene film layer is 200-400 nm.

Citation Information

Patent Citations

  • Photovoltaic module with high photoelectric conversion efficiency

    CN108461561A

  • Controllable light-absorbing graphene-like molybdenum disulfide-based switchable ecological glass and preparation method

    CN109399953A

  • Method for manufacturing high-precision ultrathin glass through rotary single-side etching and glass

    CN111253076A

  • Graphene / molybdenum disulfide composite material and liquid phase preparation method thereof

    CN111410230A

  • Composite glass as well as preparation method and application thereof

    CN114735945A